Safe passage travel companion - Safe Travel Institute; Corner Booth Productions; Safe Harbor Publishing ([S.l.] : Safe Harbor Publishing, 2005)
Whether you travel domestically or internationally, our safe travel strategies and techniques will allow you to travel with confidence. The Safe Passage Travel Companion system, guides yo through the key stages of travel. Beginning with what to pack, this guide covers how to increase your security in hotels, how to spot and avoid scams and what to do if lightning does strike and you are abducted. From robbery to hostage taking, most victims have been watched and chosen. Learn ways to make yourself an unattractive target for thieves and terrorists. Created by security experts entrusted with keeping the United States Diplomatic Corps safe, the Safe Passage Travel Companion system includes: instructional DVD with principles and strategies for safe travel; resource CD with vital information including emergency contact procedures and key embassy phone numbers; pocket reference with strategic reminders for safe travel; travel security pouch; and free online membership to the Safe Passage NewsLine for updated travel security information and resources. - Container.
DVD: -- Introduction -- Before you go -- In transit -- In country -- If lightning strikes -- Coming home.
DVD.
Keywords: Travel -- Handbooks, manuals, etc; DVDs